Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Establishing a basis for recognising marine ‘other effective area-based conservation measures’ (OECMs) in South Africa - SP Kirkman; P Kowalski; SD Holness; LJ Atkinson; R Brand; L Dunga; TP Fairweather; T Goldman; D Marnewick; J Nhleko; R Peter; C Smith; et al. (African Journal of Marine Science, 2025)

Cross-realm biodiversity profile of the South African coastal zone - LR Harris; JB Adams; A Dayaram; LV Dunga; N Job; SP Kirkman; SJ Lamberth; MC Pfaff; JL Raw; GM Rishworth; A Robbins; KJ Sink; et al. (African Journal of Marine Science, 2025)

Continental subduction controls regional magma heterogeneity and distribution of porphyry deposits in post-collisional settings - Christian G. Soder; Jerry Dunga; Rolf L. Romer (Geochimica et Cosmochimica Acta, 2024)